El flujo neto de turistas y el saldo neto de divisas por turismo en el Perú periodo 2019-2023 - Cornelio Chujutalli, Jenifer Patricia (2025)
Peru is an ancient country with many historical and natural tourist attractions, which, if properly exploited, can generate significant economic revenue for the country, but this requires organizing the activity. This doctoral thesis aims to investigate the existence of an association between tourist flow and the net foreign exchange balance from this activity, values studied that correspond to the period 2019-2023. For this purpose, the study is proposed as quantitative in nature, but correlational due to the explanation it seeks to provide. The conclusions reached show that the tourist flow is not associated with the net foreign exchange balance produced by tourism activity, in the period 2019 2023, since the value of the Correlation Coefficient was r = 0.710636164; and the Coefficient of Determination was R2 = 0.505003758. On the other hand, recorded tourist inflows exceeded outflows during the five-year period studied, yielding a positive net balance of 470,623.00 tourists. Furthermore, the study of the geographic origin of tourists visiting Peru reveals that they primarily come from South America, with 53.26% from this region, with Chile being the country of origin for the largest number of visitors. North America ranks second with 23.95% of tourists from the United States. Regarding the balance between foreign currency inflows and outflows from tourism, the net balance was positive.